2014
DOI: 10.18551/rjoas.2014-10.01
|View full text |Cite
|
Sign up to set email alerts
|

Linking Child Health, Maternal Labour Force Participation and Household Asset Endowments in Cameroon: What the People Say

Abstract: This paper is targeted objectives: to document the determinants of child health as informed by focus group discussion, to analyze what the people say concerning the relationship between child health and maternal labour force participation, to explore the perception of the people on the effects of child health on asset accumulation and to suggest public policies on the basis of the findings. We used seven focus groups to explore what the people say based on different health domains: access to public goods; inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Later on, Baye and Fambon (2010) examined the link between parental education and child health, but they used older data coming from the Cameroon Household Consumption Survey data collected by INS in 2001. Tambi et al;(2014) used the focus group design method to link child health, maternal status on the labor market and household property in Cameroon. Their approach was non-technical since they refer to ""what people say on different health domains"", without targeting a specific child health outcome, and neglecting the rural Cameroon.…”
Section: Literaturementioning
confidence: 99%
“…Later on, Baye and Fambon (2010) examined the link between parental education and child health, but they used older data coming from the Cameroon Household Consumption Survey data collected by INS in 2001. Tambi et al;(2014) used the focus group design method to link child health, maternal status on the labor market and household property in Cameroon. Their approach was non-technical since they refer to ""what people say on different health domains"", without targeting a specific child health outcome, and neglecting the rural Cameroon.…”
Section: Literaturementioning
confidence: 99%
“…Whereas child health problems remain the leading cause of ill health and death for women of child bearing age, impoverished women, especially those living in rural zones suffer disproportionately from unintended pregnancies, maternal death and disability, sexually transmitted infections and other problems related to their reproductive system and sexual behaviour [9]. Moreover, Baye and Fambon [2] observed that, in much of the healthcare demand literature, attempts at establishing linkages between health consumption and health production (wealth accumulation, productivity) have been embarked upon outside Africa [10] whereas knowledge on these issues are widely needed by very little effort in this direction has been made using data from SSA [11] the only studies that have attempted to tackle some aspects of reproductive health care, maternal labour and wealth accumulation are Baye and Fambon [2]; Tambi et al [12].…”
Section: Literature Reviewmentioning
confidence: 99%